Il trovatore (The troubadour) an opera Novello's original octavo edition - Verdi, Giuseppe (Novello and Company, 1914)
Gardens of the palacenA ruined habitation on the borders of the biscayan mountainsnthe cloisters of conventnthe campna wing of the palace of aliaferiana gloomy dungeon